SISTEM INFORMASI REKAM MEDIS PASIEN PADA KLINIK PAKTEK DOKTER BERSAMA BERBASIS WEB - Nurjani, Yeni; Putriani, Wita; -, Elzas (JURNAL AKADEMIKA, 2023)
The Joint Doctor's Practice Clinic is a practice that serves the treatment of various diseases. In the data processing process using handwriting, so that there are problems in processing medical record data, namely to get patient information, visit information, diagnostic information and doctor information, it still takes a relatively long time because they have to search for information manually in the medical record book. The purpose of this study is to analyze the current system, in order to overcome the problems faced at the Joint Doctor's Practice Clinic, by designing a Patient Medical Record Information System at the Joint Doctor's Practice Clinic. Research Framework that will be carried out in solving the problems discussed, namely, identifying problems, data collection, data analysis, system design, implementation, system testing to the maintenance phase. The system development method uses a waterfall model, the implementation of this research uses the PHP programming language and MySQL DBMS. To produce a data processing application that is expected to facilitate the processing of medical record data and the manufacture of medical record reports